Diagnostic yield of capsule endoscopy versus magnetic resonance enterography and small bowel contrast ultrasound in the evaluation of small bowel Crohn's disease: Systematic review and meta-analysis. Issue 8 (August 2017) - Kopylov, Uri; Yung, Diana E.; Engel, Tal; Vijayan, Sanju; Har-Noy, Ofir; Katz, Lior; Oliva, Salvatore; Avni, Tomer; Battat, Robert; Eliakim, Rami; Ben-Horin, Shomron; Koulaouzidis, Anastasios
Abstract: Background and aims: Capsule endoscopy (CE), magnetic resonance enterography (MRE) and small bowel (SB) intestinal contrast ultrasound (SICUS) are the modalities of choice for SB evaluation. This study aimed to compare the diagnostic yield (DY) of CE to MRE and SICUS in detection and monitoring of SB CD through meta-analysis of the available literature. Methods: We performed a systematic literature search for trials comparing the accuracy of CE, MRE and SICUS for detection of active SB inflammation in patients with suspected and/or established CD. Only prospective studies comparing CE with another additional diagnostic modality were included in the final analysis. Pooled odds ratios (ORs) for the DY of the three modalities were calculated. Results: A total of 112 studies were retrieved; following selection, 13 studies were eligible for analysis. The DY of CE for detection of active SB CD was similar to that of MRE (10 studies, 400 patients, OR 1.17; 95% CI 0.83–1.67) and SICUS (5 studies, 142 patients, OR 0.88; 95% CI 0.51–1.53). The outcomes were similar for the subgroups of suspected versus established CD and adult versus pediatric patients. CE was superior to MRE for proximal SB CD (7 studies, 251 patients, OR 2.79; 95% CI 1.2–6.48); the difference vs SICUS was not significant. Conclusion: CE, MRE and SICUS have similar DY for detection of SB CD in both suspected and established CD. CE is superior to MRE for detection of proximal SB disease, however the risk of capsule retention should be considered.